2000
DOI: 10.1016/s0092-8674(00)80670-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Rho Family GTP-Binding Protein Cdc42 in Complex with the Multifunctional Regulator RhoGDI

Abstract: The RhoGDI proteins serve as key multifunctional regulators of Rho family GTP-binding proteins. The 2.6 A X-ray crystallographic structure of the Cdc42/RhoGDI complex reveals two important sites of interaction between GDI and Cdc42. First, the amino-terminal regulatory arm of the GDI binds to the switch I and II domains of Cdc42 leading to the inhibition of both GDP dissociation and GTP hydrolysis. Second, the geranylgeranyl moiety of Cdc42 inserts into a hydrophobic pocket within the immunoglobulin-like domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
514
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(547 citation statements)
references
References 37 publications
29
514
1
3
Order By: Relevance
“…We observed that phosphorylation of RhoGDI by Src does not occur with preformed Rho GTPase-RhoGDI complexes, but requires RhoGDI to be in the uncomplexed state. This observation is consistent with the location of Tyr156 within an acidic region at the interface of the binding site on RhoGDI for Rho GTPases, as described in several structural analyses of GTPase-GDI complexes (Gosser et al, 1997;Keep et al, 1997;Hoffman et al, 2000). As a consequence of phosphorylation at Tyr156, we show that binding of RhoGDI to Rho GTPases (RhoA, Rac1, and Cdc42) is substantially reduced, both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that phosphorylation of RhoGDI by Src does not occur with preformed Rho GTPase-RhoGDI complexes, but requires RhoGDI to be in the uncomplexed state. This observation is consistent with the location of Tyr156 within an acidic region at the interface of the binding site on RhoGDI for Rho GTPases, as described in several structural analyses of GTPase-GDI complexes (Gosser et al, 1997;Keep et al, 1997;Hoffman et al, 2000). As a consequence of phosphorylation at Tyr156, we show that binding of RhoGDI to Rho GTPases (RhoA, Rac1, and Cdc42) is substantially reduced, both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…Complexation of Rho, Rac, or Cdc42 with GDIs inhibits GDP dissociation and localizes GTPases to the cytosol in inert forms unable to interact with GEFs (guanine nucleotide exchange factors), GAPs (GTPase activating proteins), or effector targets (Van Aelst and Souza-Schorey, 1997;DerMardirossian and Bokoch, 2005). GDIs maintain Rho GTPases as soluble cytosolic proteins by forming high-affinity complexes that mask the C-terminal geranylgeranyl membrane-targeting moiety within a hydrophobic pocket formed by the immunoglobulin-like domain of RhoGDI (Gosser et al, 1997;Keep et al, 1997;Hoffman et al, 2000). When Rho proteins are released from GDIs, they insert into the membrane lipid bilayer through their isoprenylated and polybasic C-terminal domains to be activated by membrane-associated GEFs, initiating the association with effector targets at the membrane.…”
mentioning
confidence: 99%
“…Although protein prenylation may facilitate anchoring of proteins to lipid membranes, data suggesting its role in protein interaction and activation are accumulating (12,17,19,28,30,38). Our data support the proposition of Magee and Seabra (26), which stresses the role of prenyl groups in protein- protein FIG.…”
Section: Discussionsupporting
confidence: 82%
“…Although C3bot does not directly interact with the guanine diphosphate, it stabilizes nucleotide binding indirectly through its interaction with the switch II region of Ral. A similar mode of nucleotide stabilization had been observed previously for two GDIs of the Rab family proteins (Rak et al 2003(Rak et al , 2004) and for RhoGDI (Hoffman et al 2000), suggesting that C3bot could act to Ral in a GDI-like manner. A structural comparison of known GDI complexes with Ral amd C3bot is shown in Fig.…”
Section: Non-enzymatic Interaction Of C3-like Exoenzymes With Ralsupporting
confidence: 82%
“…6 GTPase recognition of GDIs and a GDI-like acting toxin. The crystal structures of Ral in complex with C3bot (Pautsch et al 2005), the Rablike GTPase Ypt1 in complex with RabGDI (Rak et al 2003), and Cdc42 with RhoGDI (Hoffman et al 2000) are shown in an identical orientation relative to the GDP-bound GTPase. All three regulators bind to the GTPase effector binding region, in particular switch II, but differ in their detailed molecular mode of action.…”
Section: Non-enzymatic Interaction Of C3-like Exoenzymes With Ralmentioning
confidence: 99%